THE EFFECTIVENESS OF 4-LAYER COMPRESSION DRESSING ON HEALING IN PATIENTS WITH CHRONIC LEG ULCERS (The Research of Medical Science Review, 2025)
Objective: To provide a comprehensive descriptive analysis of the healing outcomes in patients with chronic leg ulcers treated with a four-layer compression dressing over a 24- week study period. Study Design: A descriptive case series. Settings and Duration of Study: Department of General Surgery, Sir Ganga Ram Hospital Lahore, from 22-06-2024 to 21-12-2024. Methods: Total 80 patients of 15-70 years age, having venous leg ulcers of >1cm2 and ankle-brachial index >0.8 were selected and consent taken. Demographic data, PUSH score, and history of diabetes, hypertension and smoking were documented. All patients underwent a standardized treatment by application of a four-layer compression dressing with 40mmHg compression pressure. Patients were followed up for 3 months. Endpoint was determined based on the PUSH tool. The grades of 0,1 and 2 were labelled as healing. All data collected in this study was analyzed using SPSS v.27.0. To account for potential effect modifiers like age, gender, ulcer area, duration, weight, diabetes, hypertension, and smoking, stratification was employed and Chi-square test was applied and p≤0.05 was significant. Results: Mean PUSH score after 3 months of treatment was 3.07±2.60 and ulcer healing was observed in 49 (61.3%) of the patients. Conclusion: The 4-layer compression dressing had significant role in chronic venous ulcer healing over 12 weeks period, especially in younger age groups as well as non- diabetic, normotensive and non-smoker patients with less than 12 weeks duration of ulcers.